2021
DOI: 10.1177/02601060211014127
|View full text |Cite
|
Sign up to set email alerts
|

Low serum lycopene, and adequate α-tocopherol levels in patients with psoriasis: A cross-sectional study

Abstract: Background: Psoriasis is a chronic, immune-mediated skin disease. It affects skin and joints, characterized by abnormal hyperproliferation of keratinocytes. The worldwide prevalence of psoriasis ranges from 2% to 4%. Environmental factors as smoking, alcohol consumption obesity can also work as triggers. During the inflammatory process, there is an exacerbated formation of free radicals and antioxidants are required to maintain redox balance. Aim: Assess antioxidant profiles. Methods: A cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Physical activity has a non‐secondary role on the general approach of psoriasis and its associated comorbidites, and weight loss may lead to psoriasis improvement and enhance the efficacy of systemic treatments 7,11 . Undoubtedly, a healthy lifestyle should also be based on a proper dietary program combining calories restriction with the preferential intake of food with high antioxidant properties, such as fish rich in ω‐3 PUFAs, fruits and vegetables, avoiding that with a potential proinflammatory action 7,11,21,48,49 . Oral vitamin D supplementation and gluten‐free diet are only recommended for patients with documented hypovitaminosis and increased serum AGA antibody levels, respectively, 7,49 whereas prebiotics and probiotics, also regarded as potentially beneficial in psoriasis, represent a new developing area of investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity has a non‐secondary role on the general approach of psoriasis and its associated comorbidites, and weight loss may lead to psoriasis improvement and enhance the efficacy of systemic treatments 7,11 . Undoubtedly, a healthy lifestyle should also be based on a proper dietary program combining calories restriction with the preferential intake of food with high antioxidant properties, such as fish rich in ω‐3 PUFAs, fruits and vegetables, avoiding that with a potential proinflammatory action 7,11,21,48,49 . Oral vitamin D supplementation and gluten‐free diet are only recommended for patients with documented hypovitaminosis and increased serum AGA antibody levels, respectively, 7,49 whereas prebiotics and probiotics, also regarded as potentially beneficial in psoriasis, represent a new developing area of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…7,11 Undoubtedly, a healthy lifestyle should also be based on a proper dietary program combining calories restriction with the preferential intake of food with high antioxidant properties, such as fish rich in ω-3 PUFAs, fruits and vegetables, avoiding that with a potential proinflammatory action. 7,11,21,48,49 Oral vitamin D supplementation and gluten-free diet are only recommended for patients with documented hypovitaminosis and increased serum AGA antibody levels, respectively, 7,49 whereas prebiotics and probiotics, also regarded as potentially beneficial in psoriasis, represent a new developing area of investigation. Promising investigations also point to a role of dietary interventions in the modification of aberrant miRNA expression in psoriasis, since bioactive compounds may lead to psoriasis improvement by proficiently affecting microRNA expression.…”
Section: Interventionsmentioning
confidence: 99%
“…Nutritional status is an essential factor in the management of certain skin diseases; therefore, there is a growing interest in managing psoriasis through diet [ 6 ]. Some diets might have a positive impact on psoriasis because they tend to prevent inflammatory conditions in general [ 7 , 8 ]. Additionally, a number of studies suggest including vitamin supplements during psoriasis treatments, with limited amount of evidence supporting direct benefits [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a number of studies suggest including vitamin supplements during psoriasis treatments, with limited amount of evidence supporting direct benefits [ 9 , 10 ]. Studies have reported that diets enriched with antioxidants, beta-carotene, vitamin-C, phenolics and flavonoids, which can be found in natural products, help to improve dermatological lesions [ 7 , 8 , 9 , 10 ]. Certain vitamins exhibit hydrophilic antioxidant activity, whereas others hinder lipid peroxidation from spreading.…”
Section: Introductionmentioning
confidence: 99%